2018
DOI: 10.1002/dta.2513
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of the ActRII‐Fc fusion proteins Sotatercept (ActRIIA‐Fc) and Luspatercept (modified ActRIIB‐Fc) in serum by means of immunoaffinity purification, tryptic digestion, and LC‐MS/MS

Abstract: Therapeutic proteins are a continuously growing class of pharmaceuticals and comprise several drug candidates with potential performance-enhancing properties. In particular, activin receptor competitors, such as the ActRII-Fc fusion proteins Sotatercept (ActRIIA-Fc) and Luspatercept (modified ActRIIB-Fc), have the potential for being misused as doping agents in sports as they were found to inhibit negative regulators of late-stage erythropoiesis.Within this study, ammonium sulfate precipitation, immunoaffinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In accordance with earlier studies, antigen‐coupled magnetic beads were used to facilitate enrichment and isolation of Domagrozumab from the biological matrix. As myostatin shares a high degree of sequence homology with other TGF‐β cytokines, the affinity of Domagrozumab for myostatin, activin A, and GDF‐11 (all obtained from PeproTech, Hamburg, Germany) was investigated by means of Western blotting.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In accordance with earlier studies, antigen‐coupled magnetic beads were used to facilitate enrichment and isolation of Domagrozumab from the biological matrix. As myostatin shares a high degree of sequence homology with other TGF‐β cytokines, the affinity of Domagrozumab for myostatin, activin A, and GDF‐11 (all obtained from PeproTech, Hamburg, Germany) was investigated by means of Western blotting.…”
Section: Methodsmentioning
confidence: 97%
“…During method optimization, different amounts of the cytokine were tested in combination with NHS magnetic sepharose beads (GE Healthcare). By using an earlier published protocol based on the manufacturer's instructions, 1, 2.5, 5, and 10 μg of GDF‐11 were coupled to 25 μL of magnetic beads, which were subsequently employed for the extraction of serum samples containing 1 μg/mL of Domagrozumab. Western blot analysis (see section 2.5) using both dimeric myostatin and GDF‐11 as bait proteins showed that the sensitivity increases with the amount of ligand coupled to the beads.…”
Section: Methodsmentioning
confidence: 99%
“…A semi‐dry Western blot was conducted, and target analytes were detected by means of biotinylated primary antibodies directed against sotatercept and luspatercept in combination with a streptavidin‐horseradish peroxidase complex, yielding an overall accelerated and cost‐effective test method for TGF‐β inhibitors. Complementary to these approaches, Walpurgis et al presented a test method for the detection of sotatercept and luspatercept in human serum by mass spectrometry‐based strategies . A volume of 200 μL of serum was subjected to ammonium sulfate precipitation, and target analytes were extracted from the obtained particulate by means of magnetic nanoparticles coated with anti‐ActRIIA and ‐ActRIIB antibodies.…”
Section: Peptide Hormones Growth Factors Related Substances and MImentioning
confidence: 99%
“…Compound‐dedicated confirmatory analyses of the same analytes from dried blood spots consisted of the extraction of the spots into ammonium bicarbonate solution with subsequent ammonium sulfate precipitation of the IgG content and immunoaffinity purification of the particulate by activin A‐coated magnetic nanoparticles. After tryptic digestion, diagnostic peptides were determined by LC‐HRMS(/MS) analysis using similar instrumental conditions as presented by Walpurgis et al The LOD of the assays were found to be 250 ng/mL, and the application of the test method to clinical trial post‐administration samples containing bimagrumab provided proof‐of‐concept with the unequivocal detection of the drug candidate in specimens sampled after subcutaneous as well as intravenous administration.…”
Section: Peptide Hormones Growth Factors Related Substances and MImentioning
confidence: 99%
“…Pilot study data outlined the capability of a higher sample throughput than obtained using conventional gel electrophoretic approaches, but method optimization and assessment is still ongoing. In addition, options enabling the coverage of new ESA drug candidates such as sotatercept and luspatercept, preferably by means of established assays, was shown by Reichel et al and Walpurgis et al Both immunological methodologies and combined immunopurification/chromatography mass‐spectrometry‐based approaches were shown to provide fit‐for‐purpose analytical means enabling detection limits substantially below expected serum concentrations.…”
mentioning
confidence: 99%